Analisis Bentuk Kepemilikan Bahasa Patani di Halmahera Tengah - Nurain Jalaluddin; Ety Duwila (Humanitatis : Journal of Language and Literature, 2021)
This study aims to describe the possessive forms of Patani language. In describing the data, the researchers apply the three method stages; the method of data acquisition, data analysis, and presentation of analysis. The result of the study shows that the possessive forms of Patani language are 1) :-g, -nik, -nak for the first person singular; 2) the possessive forms of first-person plural for exclusive is only -mam and there are three forms for inclusive: -r, -nir, -nor; 4) for the second person singular are:-m, -nim, -nam; 5) the second person plural is -me, -nimi, -nomo; 6) the possessive forms: I -, -ni, -no is for the third person singular; 7) for third person plural, the forms are -re, -niri, and -noro. Most of the possessive forms are enclitic, the only proclitic in this study is the possessive form of third-person singular I-.